Maturation of the GABAergic Transmission in Normal and Pathologic Motoneurons - Anne-Emilie Allain; Hervé Le Corronc; Alain Delpy; William Cazenave; Pierre Meyrand; Pascal Legendre; Pascal Branchereau (Neural Plasticity)
γ-aminobutyric acid (GABA) acting on Cl−-permeable ionotropic type A (GABAA) receptors (GABAAR) is the major inhibitory neurotransmitter in the adult central nervous system of vertebrates. In immature brain structures, GABA exerts depolarizing effects mostly contributing to the expression of spontaneous activities that are instructive for the construction of neural networks but GABA also acts as a potent trophic factor. In the present paper, we concentrate on brainstem and spinal motoneurons that are largely targeted by GABAergic interneurons, and we bring together data on the switch from excitatory to inhibitory effects of GABA, on the maturation of the GABAergic system and GABAAR subunits. We finally discuss the role of GABA and its GABAAR in immature hypoglossal motoneurons of the spastic (SPA) mouse, a model of human hyperekplexic syndrome.